Reflorestamento compensatório com vistas à retençãode água no solo da bacia hidrográfica do Córrego Palmital, Jaboticabal, SP - Borges, Maurício José; Pissarra, Teresa Cristina Tarié [UNESP]; Valeri, Sérgio Valiengo [UNESP]; Okumura, Edson Mitsuo [UNESP] (My University, 2005)
This work had as objective to quantify the reforestation for water retention in the Palmital Stream watershed, County of Jaboticabal, SP, by using the methodology of compensatory forestation for retention of water in watersheds. This methodology esteems the retention of water in watersheds considering the world medium value of destiny of the water in the hydrologic cycle, the use/occupation of the soil (forest, pasture and agriculture) and its permeability. The watershed in this study presents an area of 10,625.21 ha, being 237.75 ha at forest, 467.01 ha in pasture and 9,237.57 ha in agriculture. The medium values of the permeability identified in the soils were of 94.81 mm h -1 in forest, 8.99 mm t -1 in pasture and 36.01 mm h -1 in agriculture (sugar cane). Considering that should infiltrate in the soil 20.55% of the water that precipitates on the watershed, and, that the losses of water in forest areas is considered standard, the total estimated volume to compensate the excessive loss that occur in the areas of pasture and agriculture is 12.21 million of m 3ano. The compensatory forestation to retain that volume of loss should contemplate an area of 942.73 ha (8.87% of the area of the watershed). The reforestation can be priority in permanent conservation area or in areas of Legal Reserve.
Compensatory reforestation for water retention in the Palmital watershed, Jaboticabal, SP
Keywords: Fotointerpretation; Soil permeability; Soil use/ occupation; Hydrologic cycle; Soil occupation; Soil use; Water retention; Agriculture; Forestry; Soils; Water conservation; Watersheds; Reforestation; Soil; Water Management